Y-z=x-y

Simple and best practice solution for Y-z=x-y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Y-z=x-y equation:


Simplifying
Y + -1z = x + -1y

Solving
Y + -1z = x + -1y

Solving for variable 'Y'.

Move all terms containing Y to the left, all other terms to the right.

Add 'z' to each side of the equation.
Y + -1z + z = x + -1y + z

Combine like terms: -1z + z = 0
Y + 0 = x + -1y + z
Y = x + -1y + z

Simplifying
Y = x + -1y + z

See similar equations:

| 17x+60=9x+36 | | 5/24=10/g | | 4/9a=1/9a-5/6 | | 5n-6=-106 | | 14x-76=8x-40 | | -6x-28=-3x-16 | | 0.09xX=72.44 | | -18x-83=-12x-47 | | -8x+32=-5x+17 | | h-6.5=15.2 | | 4y-3x=-84 | | -5x+26=-3x+16 | | 52=w/4 | | 9x+36=6x+18 | | F(x)=-1(x+1)(x-7) | | 3x+37=11.25 | | -18x+31=-12x+19 | | cos70=14/x | | 48-4x=7x | | 2-(x+1)=2x-11 | | 6(3x-2)=3-2(4x+1) | | -9x+9=-6x+6 | | m/2=27 | | 7x+4=7(8)+4 | | 6(w-2)=-7w-25 | | 19x-79=12x-44 | | 8(-2x+3)=32 | | 80-2x=50 | | x-.3x=38000 | | -15x-125=-9x-83 | | -3k^2=-75 | | 6a^2-8ab=0 |

Equations solver categories